Fabrication and high‐resolution electron microscopy study of FePt L10/A1 graded exchange spring media. Issue 7 (22nd April 2013) - Lee, Jehyun; Dymerska, Barbara; Fidler, Josef; Alexandrakis, Vasilis; Speliotis, Thanassis; Niarchos, Dimitris; Pongratz, Peter; Suess, Dieter
<x xml:space="preserve">Abstract</x> We have prepared FePt L10/A1 exchange spring graded media by controlling deposition temperature. The performance of the media was determined by the deposition conditions, particularly the cooling rate. By varying the deposition conditions a coercivity of 4.0 kOe was achieved without loss in remanent magnetization, the value corresponds to 88% reduction compared with that of FePt L10 single phase (32.2 kOe). High‐resolution transmission electron microscopy (HRTEM) investigations have revealed that this drastic coercivity reduction originates from the unique microstructure of the specimens: coexistence of the L10 and A1 phases at the interphase boundary. In this region the two phases are dispersed one into another like inclusions in a matrix. Finally, the role of the complicated phase boundary on switching field reduction was discussed using micromagnetic simulations. <inline-graphic xlink:href="ark:/27927/pgg277v25sp" content-type="pssa201228731-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />